PERAN BAHASA INDONESIA DALAM PROSES SOSIALISASI RADIKALISME DI SMAN 5 PEKANBARU - Ratu Husna Aulia; Nabila Ariyanda; Yuhelsa Marsanda; Tiara Syahfitri; Zahratul Alya Anwar; Zakia Aulia Zikra; Lexa Putri Amanda; Aufa Nur Asyifa; Ripi Hamdani (CV. Denasya Smart Publisher, 2026)
The formal education system in Indonesia, from kindergarten to senior high/vocational schools, is not immune to the spread of radicalism. Education has become one of the